(3hUjI dSGf GdOjf Hf GdWjH dGhdGOgs - (3CHh YHO Gddg eMeO Hf YHO Gddg Hf SYjO GdZQfGWis; (3CHhYHO Gddg eMeO Hf YHO Gddg Hf SYjO GdSdeGfi GdZQfGWi GdCfOdSj, GdTgjQ HdSGf GdOjf Hf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GHf GdNWjH QVi Gddg Yfg GdMeO ddg GdPi dGjQhYg GdMeGe GdeQbhH hGfi deG YdGfi GdeTjH HYeJg s
(3BNQgG (B:s
(3hGdSdGe Ydjce ef MHjHce GdehOY hGdOce eMeO Hf YHO Gddg GHf GdNWjH hQMeI Gddg hHQcGJg ced GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdCOHs